Oligodendrocytes in a Nutshell - Michalski, John-Paul; Kothary, Rashmi (Frontiers in Cellular Neuroscience, 2015)
Oligodendrocytes are the myelinating cells of the central nervous system (CNS). While the phrase is oft repeated and holds true, the last few years have borne witness to radical change in our understanding of this unique cell type. Once considered static glue, oligodendrocytes are now seen as plastic and adaptive, capable of reacting to a changing CNS. This review is intended as a primer and guide, exploring how the past five years have fundamentally altered our appreciation of oligodendrocyte development and CNS myelination.